The bonds of love : St. Peter Damian's theology of the spiritual life - Mursell, Gordon (The Catholic University of America Press, 2021)
"Explores the spirituality of St. Peter Damian, a reformer of church and society in the Middle Ages; explores tension between a call to solitude and holiness and a call to prophetic social and ecclesial engagement"--